Self-Compassion and Mindfulness Among Young Mothers: A Phenomenological Study in Padang, Indonesia - Nur Hisna Daniati; Afdal Afdal; ⁠Zadrian Ardi; Miftahul Fikri (Scidacplus, 2026)
Young mothers aged 18–25 are vulnerable to psychological stress due to role transitions and a lack of emotional readiness. Self-compassion and mindfulness are two psychological approaches that mutually support individual well-being; however, research on how these are actually experienced by young mothers in Indonesia remains very limited. This study aims to describe the nature of self-compassion, describe the nature of mindfulness, and analyze the relationship between the two in the experiences of young mothers in Padang City. This study employs a qualitative approach using the phenomenological method. The primary informants consist of 5 young mothers, 2 husbands, and 2 parents of the young mothers as supporting informants, selected through snowball sampling. Data were collected through observation, in-depth interviews, and document analysis. Data analysis involved data reduction, data presentation, and drawing conclusions with the assistance of NVivo 15 software. Data validity was tested through source triangulation. The results of this study indicate that self-compassion is most strongly manifested in the forms of physical self-care (self-kindness), a sense of shared humanity, and the management of emotions and mindfulness. These aspects develop through four dimensions: observing, describing, acting with awareness, and accepting without judgment, with variations influenced by personality and social support. These findings suggest that the development of self-compassion and mindfulness in young mothers should be approached simultaneously and involve strong social support.